Dissemination of l. S. Vigotski's cultural-historical theory in Brazil - Prestes, Z.; Tunes, E.; Beck, M.T. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Abstract only Context and relevance. The article presents brief information on how the works of L. S. Vygotsky and his collaborators arrived and spread in Brazil and data from a survey on the Platform of the National Council for Scientific and Technological Development of the National Agency for Scientific and Technological Research (CNPq), more specifically, on the Directory of Research Groups (DGP) which records data and production of research groups in Brazil. Objective. The survey focused on research groups in the areas of education and psychology and sought to identify Brazilian research groups that indicate, in their titles and summaries of activities, that they carry out research based on the cultural-historical theory of L. S. Vygotsky. Methods and materials. We carried out a survey to see how many research groups are active in Brazil working with cultural-historical theory, specifically in the areas of education and psychology. The survey was carried out through a series of searches on the DGP-CNPq's parameterized consultation page, between June 1 and 10, 2025. Results. The survey showed that of the total of 154 groups found according to the descriptors chosen, 140 groups (90.9%) are in public educational institutions and 14 (9.1%) in private institutions. This data shows the importance that public educational institutions attach to recording activities carried out by groups of their researchers. Conclusions. Although the arrival of Vygotsky's works in Brazil took place almost 40 years ago, the dissemination of his thought unfortunately took place based on translations and editions that mutilated his writings and thus misrepresented important ideas from his studies and theoretical-methodological investigations. The survey presented in this text does not go into this issue in depth, nor does it discuss the bibliographical references used in the intellectual production of the research groups registered with DGP-CNPq. We have restricted ourselves to some more general aspects of the current scenario, even though we know, as has been pointed out, that it does not correspond exactly to reality. Контекст и актуальность. В статье представлен краткий обзор того, как работы Л.С. Выготского и его соавторов появились и распространились в Бразилии, а также данные опроса, проведенного на платформе Национального совета по научным и технологическим разработкам (CNPq), а именно в разделе «Каталог исследовательских групп» (DGP), который регистрирует данные и результаты деятельности исследовательских групп в Бразилии. Цель. Опрос был направлен на выявление исследовательских групп в области образования и психологии, которые содержат в названиях и описаниях своих работ информацию о том, что они проводят исследования на основе культурно-исторической теории Л.С. Выготского. Методы и материалы. Мы провели опрос, чтобы определить, сколько исследовательских групп активно работают с культурно-исторической теорией в Бразилии, особенно в областях образования и психологии. Опрос осуществлялся посредством серии поисковых запросов на странице параметризованной консультации DGP-CNPq4 в период с 1 по 10 июня 2025 года. Результаты. Опрос показал, что из общего числа найденных 154 групп, согласно выбранным дескрипторам, 140 групп (90,9%) находятся в государственных образовательных учреждениях и 14 (9,1%) - в частных учреждениях. Эти данные демонстрируют важность, которую придают государственные образовательные учреждения регистрации деятельности своих исследовательских групп. Выводы. Хотя работы Выготского появились в Бразилии почти 40 лет назад, распространение его идей, к сожалению, происходило на основе переводов и изданий, искаженных и урезанных, что привело к неправильному представлению о важных идеях его исследований и теоретико-методологических разработок. Представленный в этом тексте опрос не углубляется в этот вопрос и не рассматривает библиографические источники, использованные в научной деятельности зарегистрированных в DGP-CNPq исследовательских групп. Мы ограничились некоторыми более общими аспектами текущей ситуации, хотя и осознаем, как было отмечено ранее, что она не полностью соответствует реальности.